THE UTILISATION OF E-LEARNING TO IMPROVE CONTRACEPTIVE SELECTION SELF-EFFICACY POSTNATAL MOTHERS - Dewi Mayangsari; Aprilia Kusumawati; Sa'adah Mujahidah (Universitas Karya Husada Semarang, 2024)
The inadequate prevalence of postpartum contraceptive utilization is attributable to insufficient communication, information, and educational services. E-learning media warrants consideration due to its cost-effectiveness and ability to present knowledge in an appealing fashion, which influences the recipient's self-efficacy for postpartum contraception. This study aimed to analyze the effectiveness of family planning counseling media with e-learning on postpartum contraceptive selection at Wonosamudro Public Health Center. Qualitative research type Quasi-experimental approach. This research employs a pre-test and post-test group design. The populace of postpartum mothers in the Wonosamudro Health Center working area in 2023 was 386 patients; the inclusion criteria were postpartum mothers after 14 days postpartum, giving birth for the first time either average or Sectio Caesaria. The number of research samples was 80 respondents. The univariate analysis uses central tendency data, and the bivariate analysis uses the Paired T-Test test because the normality test results are typical (p value> 0.05). The results showed that after debriefing/education and follow-up via WhatsApp group and TikTok, there was a significant increase in scores (35.24). The significance level (2-tailed) of 0.000 (<0.05) indicates a substantial difference (meaningful influence) between before and after e-learning in the selection of postpartum contraception.